Research on the network structure and gender/age differences of psychological safety among urban residents: network analysis based on a large sample - Tao Yang; Huicong Cai; Juan Song; Na Li; Haiyan Liu (BMC Psychology)
Abstract Background Psychological safety as the key to mental health, not only affects individual happiness and quality of life but also relates to social stability and harmony. However, psychological safety is complex and multidimensional, with unclear internal structures and influencing factors and insufficient research on gender and age differences. Urban residents are living in an environment characterized by fast-paced, high-pressure, multicultural integration, and complex social relationships. Therefore, in-depth exploration of its core dimensions and network structure is crucial for formulating effective mental health strategies and enhancing residents’ sense of psychological safety. Methods A survey was conducted on 9,282 urban residents using the Psychological Safety Scale. Using R version 4.3.2 for network estimation, centrality estimation, accuracy and stability estimation, and network comparison. Results The results found that the strength centrality index of the general sense of safety dimension is always the highest in the total network and networks of different genders and ages. The network comparison results show that there are significant gender and age differences in the dimensions/item networks of psychological safety. There are connections between trust and relaxation, excitement, and calmness in the dimension network of male samples, while there are no such connections in the dimension network of female samples. The general sense of safety and relaxation connection strength on the male dimension network is significantly stronger than that on the female dimension. In the dimension network of the youth sample, the strength of the connection between calmness and relaxation, trust and relaxation were significantly stronger than those of the middle-age sample, while the strength of the connection between relaxation and excitement was significantly weaker than that of the middle-age sample. Conclusion Researchers should fully consider gender and age factors and adopt more personalized and differentiated strategies for promoting individual psychological safety.